Akibat-Akibat Hukum terhadap Pelaku Tindak Pidana Pemalsuan Rekam Medis Seseorang - Mario Gregorius Funan Ahoinnai; I Nyoman Sugiartha; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2020)
Health services especially in the medical world, patients who feel that the services provided are not satisfactory even cause fatal conditions to the detriment of patients caused by paramedic errors, then the patient's family must make a firm effort, plus if the patient's rights feel not given. The purpose of this study was to determine the legal consequences of falsification of medical records of the origin of a person and the responsibility of hospitals that participated in helping falsify medical records. In this study using the type of normative legal research by analyzing and knowing the law becomes a set of rules a positive norm in the legislation system. The legal consequences of falsifying a person's medical record are not clearly regulated in regulations relating to the falsification of a person's medical record, it is not clearly regulated in Wetboek van Statrecht (KUHP), but a medical record is a confidential document in the event of falsification of documents or a letter has been regulated in Article 263 of the Criminal Code which explicitly convicts anyone found guilty of falsifying a letter. The responsibility of the hospital which also falsified the medical record is a criminal justice process to prove the elements of wrongdoing in a criminal act to be accounted for because it has been regulated in Law Number 36 of 2014 concerning Health Workers contained in article 84 which contains actions which occurs due to negligence committed by a nurse doctor or health worker.